2014
DOI: 10.1007/s10495-014-0997-9
|View full text |Cite
|
Sign up to set email alerts
|

H2AX phosphorylation regulated by p38 is involved in Bim expression and apoptosis in chronic myelogenous leukemia cells induced by imatinib

Abstract: Increasing evidence suggests that histone H2AX plays a critical role in regulation of tumor cell apoptosis and acts as a novel human tumor suppressor protein. However, the action of H2AX in chronic myelogenous leukemia (CML) cells is unknown. The detailed mechanism and epigenetic regulation by H2AX remain elusive in cancer cells. Here, we report that H2AX was involved in apoptosis of CML cells. Overexpression of H2AX increased apoptotic sensitivity of CML cells (K562) induced by imatinib. However, overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Resveratrol induced p38 and JNK phosphorylation in a time-dependent manner (Figure 2), following a response similar to that for H2AX phosphorylation ( Figure 1A). Unexpectedly, resveratrol strongly inhibited ERK phosphorylation (Figure 2), which is activated by BCR-ABL with constitutively active tyrosine kinase activity in CML cells [25] . This finding is not consistent with the results reported by Mustafi et al, indicating that resveratrol stimulates ERK activity in K562 cells [29] .…”
Section: Resveratrol Induces H2ax Phosphorylation and Apoptosis In K5mentioning
confidence: 89%
See 4 more Smart Citations
“…Resveratrol induced p38 and JNK phosphorylation in a time-dependent manner (Figure 2), following a response similar to that for H2AX phosphorylation ( Figure 1A). Unexpectedly, resveratrol strongly inhibited ERK phosphorylation (Figure 2), which is activated by BCR-ABL with constitutively active tyrosine kinase activity in CML cells [25] . This finding is not consistent with the results reported by Mustafi et al, indicating that resveratrol stimulates ERK activity in K562 cells [29] .…”
Section: Resveratrol Induces H2ax Phosphorylation and Apoptosis In K5mentioning
confidence: 89%
“…Therefore, the MAPK pathways have become a focus of intense investigation for developing small-molecule inhibitors as targeted therapeutics [28] . Our previous data demonstrated that p38 MAPK is involved in imatinib-induced apoptosis in CML cells [25] . In the current study, we investigated the role of MAPK pathways (ERK, p38, and JNK) in apoptosis and in H2AX phosphorylation in CML cells induced by resveratrol.…”
Section: Resveratrol Induces H2ax Phosphorylation and Apoptosis In K5mentioning
confidence: 96%
See 3 more Smart Citations